2018
DOI: 10.1002/chem.201705316
|View full text |Cite
|
Sign up to set email alerts
|

Iron Precatalysts with Bulky Tri(tert‐butyl)cyclopentadienyl Ligands for the Dehydrocoupling of Dimethylamine‐Borane

Abstract: In an attempt to prepare new Fe catalysts for the dehydrocoupling of amine-boranes and to provide mechanistic insight, the paramagnetic Fe dimeric complex [Cp'FeI] (1) (Cp'=η -((1,2,4-tBu) C H )) was used as a precursor to a series of cyclopentadienyl Fe and Fe mononuclear species. The complexes prepared were [Cp'Fe(η -Tol)][Cp'FeI ] (2) (Tol=C H Me), [Cp'Fe(η -Tol)][BAr ] (3) (BAr =[B(C H (m-CF ) ) ] ), [N(nBu) ][Cp'FeI ] (4), Cp'FeI (5), and [Cp'Fe(MeCN) ][BAr ] (6). The electronic structure of the [Cp'FeI ]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 84 publications
0
8
0
Order By: Relevance
“…When the reaction progress was monitored with 11 B­{ 1 H} NMR spectroscopy, 51% of the DMAB was converted to I and the linear intermediate Me 2 NH–BH 2 –NMe 2 –BH 3 ( III ) in a 1:1.2 ratio within 7 min, along with the formation of a small amount of II ; the DMAB was fully consumed within 1 h, forming mostly I along with small amounts of II and III . The catalytic activity qualifies 2 as being one of the most active Fe-based homogeneous catalysts for the dehydrogenation of DMAB . Compounds 4 and 5 display catalytic activities and product distributions comparable to those of complex 2 toward the dehydrocoupling of DMAB under the same conditions (1 mol % of 4 or 0.5 mol % of 5 ; 1 mol % of Fe; see the Supporting Information).…”
Section: Resultsmentioning
confidence: 89%
“…When the reaction progress was monitored with 11 B­{ 1 H} NMR spectroscopy, 51% of the DMAB was converted to I and the linear intermediate Me 2 NH–BH 2 –NMe 2 –BH 3 ( III ) in a 1:1.2 ratio within 7 min, along with the formation of a small amount of II ; the DMAB was fully consumed within 1 h, forming mostly I along with small amounts of II and III . The catalytic activity qualifies 2 as being one of the most active Fe-based homogeneous catalysts for the dehydrogenation of DMAB . Compounds 4 and 5 display catalytic activities and product distributions comparable to those of complex 2 toward the dehydrocoupling of DMAB under the same conditions (1 mol % of 4 or 0.5 mol % of 5 ; 1 mol % of Fe; see the Supporting Information).…”
Section: Resultsmentioning
confidence: 89%
“…Me 2 NH-BH 3 was selected as the substrate for catalytic dehydrogenation reactions, due to the simplicity of different known reaction products and the possibility to gain mechanistic insights. In recent years, a number of iron-based catalysts was reported for the dehydrogenation of amine and ammonia boranes, ranging from simple iron phosphine complexes, , such as [(Me 3 P) 3 Fe­(H)­(H 2 CPMe 2 )], to cyclopentadienyl complexes, pincer-type complexes with different kinds of ligands, monomeric , and dimeric iron­(I) complexes, complexes with β-diketiminate and P 2 N 2 -type ligands …”
Section: Resultsmentioning
confidence: 99%
“…As previous reports on iron catalysts for the dehydrogenation of Me 2 NH-BH 3 provided evidence for the formation of catalytically active nanoparticles, ,, we performed a number of poisoning experiments to get further insight in the nature of the active species. Addition of mercury to the catalytically active reaction mixture did not result in a reduced activity for 3a and 3c (entries 6 and 9).…”
Section: Resultsmentioning
confidence: 99%
“…Inorganics 2023, 11, 437 2 of 11 halido-bridged dimers [{Fe(η 5 -Cp')(µ-X)} 2 ], according to single-crystal X-ray diffraction (XRD) (Cp' = C 5 iPr 5 , X = Br; Cp' = C 5 HiPr 4 , X = Br, I; Cp' = C 5 H 2 -1,2,4-tBu 3 , X = Br, I; Cp' = C 5 (p-C 6 H 4 Et) 5 , X = Br) [26][27][28][29]. Manners and Walter independently found that [{Fe(η 5 -C 5 H 2 -1,2,4-tBu 3 )(µ-I)} 2 ] undergoes heterolytic cleavage in toluene, affording [Fe(η 5 -C 5 H 2 -1,2,4-tBu 3 )(C 7 H 8 )] + and [Fe(η 5 -C 5 H 2 -1,2,4-tBu 3 )I 2 ] − [30,31]. In the same vein, deaggregation of [{Fe(η 5 -C 5 H 2 -1,2,4-tBu 3 )(µ-I)} 2 ] was achieved through reaction with NR 4 I (R = Et, nBu), giving rise to the formation of NR 4 [Fe(η 5 -C 5 H 2 -1,2,4-tBu 3 )I 2 ] [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…Manners and Walter independently found that [{Fe(η 5 -C 5 H 2 -1,2,4-tBu 3 )(µ-I)} 2 ] undergoes heterolytic cleavage in toluene, affording [Fe(η 5 -C 5 H 2 -1,2,4-tBu 3 )(C 7 H 8 )] + and [Fe(η 5 -C 5 H 2 -1,2,4-tBu 3 )I 2 ] − [30,31]. In the same vein, deaggregation of [{Fe(η 5 -C 5 H 2 -1,2,4-tBu 3 )(µ-I)} 2 ] was achieved through reaction with NR 4 I (R = Et, nBu), giving rise to the formation of NR 4 [Fe(η 5 -C 5 H 2 -1,2,4-tBu 3 )I 2 ] [30,31]. The only other closely related compound is [Fe(η 5 -C 5 H 2 -1,2,4-tBu 3 )(µ-Br) 2 Na(DME) 2 ], which Sitzmann obtained through serendipity and in trace amounts only in the preparation of [{Fe(η 5 -C 5 H 2 -1,2,4-tBu 3 )(µ-Br)} 2 ] from [FeBr 2 (DME)] and the corresponding sodium cyclopentadienide in DME [32].…”
Section: Introductionmentioning
confidence: 99%